Glenohumeral relationships: Subchondral mineralization patterns, thickness of cartilage, and radii of curvature. Issue 11 (1st July 2013) - Zumstein, Valentin; Kraljević, Marko; Müller‐Gerbl, Magdalena
ABSTRACT Subchondral mineralization represents the loading history of a joint and can be measured in vivo using computed tomography osteoabsorptiometry. Different mineralization patterns in the glenohumeral joint have been explained by the principle of physiologic incongruence. We sought to support this explanation by measurement of mineralization, radii, and cartilage thickness in 18 fresh shoulder specimens. We found three mineralization patterns: bicentric, monocentric anterior, and monocentric central. Mean radii of the glenoids were 27.4 mm for bicentric glenoids, 27.3 mm for monocentric anterior, and 24.8 mm for monocentric central glenoids. Cartilage thickness measurement revealed the highest values in anterior parts; the thinnest cartilage was found centrally. Our findings support the principle of a physiologic incongruence in the glenohumeral joint. Bicentric mineralization patterns exist in joints consisting of more flat glenoids compared to the corresponding humeral head. Monocentric distribution with a central maximum was found in specimens with glenoids being more curved, indicating higher degrees of congruence, which might represent an early stage of degenerative disease. The obtained information might also be important for implant fixation in resurfacing procedures or to achieve the best possible fit of an osteochondral allograft in the repair of cartilage defects. © 2013 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 31:1704–1707, 2013